Multifunctional boron nitride nanosheet/polymer composite nanofiber membranes. (24th January 2019) - Yin, Chuan-Gen; Ma, Yu; Liu, Zhong-Jie; Fan, Jin-Chen; Shi, Peng-Hui; Xu, Qun-Jie; Min, Yu-Lin
Abstract: In this work, we successfully prepared multifunctional boron nitride nanosheets (BNNS)/polyvinyl alcohol (PVA) nanofiber membranes. Using sulfanilic acid (SA) as a medium, hexagonal boron nitride (h-BN) were exfoliated into SA-functionalized BNNS through dry ball-milling process followed with liquid-phase exfoliation based on Lewis acid-base interaction. The f-BNNS/PVA composite nanofiber membranes with different loading amounts of f-BNNS were prepared through electrospinning. The results demonstrated the electrospun f-BNNS/PVA composite nanofiber membranes show high mechanical properties and thermal conductivities. The yield and ultimate tensile strengths of f-BNNS/PVA composite nanofiber membrane at 5 wt% loading amount can reach ∼8.56 and ∼11.37 MPa. Meantime, the thermal conductivity of f-BNNS/PVA composite nanofiber membrane with 10 wt% loading amounts of f-BNNS is ∼0.7328 W/(mK), almost 6.47 times higher than that of neat PVA membrane. Besides, the f-BNNS/PVA composite nanofiber membrane can also be used as a filtration membrane for fast malachite green (MG) absorption and separation of MG and rhodamine B dyes. Graphical abstract: Image 1 Highlights: Sulfanilic acid facilitates the exfoliation and functionalization of boron nitride nanosheets. Electrospun functionalized boron nitride nanosheet/PVA nanofiber membranes were prepared. The membrane processes high mechanical property and thermal conductivity. The membrane can be used for fast separating the mixed dye of malachite green and rhodamine B.